Analisis Tingkat Pengetahuan dan Perilaku Swamedikasi Diare terhadap Mahasiswa Farmasi Universitas Tanjungpura: Knowledge and Behaviour Assessment of Diarrhea Self-Medication among Pharmacy Undergraduate in Tanjungpura University - Agvina Felicia Esperanza; Liza Pratiwi; Shoma Rizkifani (Jurnal Sains dan Kesehatan, 2023)
Self-medication is done to treat minor illnesses, such as diarrhea. Knowledge and behaviour of drugs usage in each individual affect self-medication so that irrational drugs usage can be prevent. This study determines the relationship between semester, knowledge and behaviour about diarrhea self-medication of pharmacy students at Tanjungpura University 2021/2022. The research method was carried out retrospectively in the form of a cross-sectioned questionnaire. Stratified random sampling method was used for sample selection. Rank-spearman analysis was used to analyze the relationship between semester level, knowledge and behaviour of diarrhea self-medication. Based on research, out of 232 respondents, majority of respondents were women, aged 21, obtained drugs from pharmacies without prescription (81,03%) and used adsorbent class for antidiarrheal drugs. Knowledges are classified from good (9,91%), moderate (28,45%) and low (61,64%). Behaviours are classified as appropiate (79,74%) and inappropriate (20,26%). The p-value results show the relationship between semester and knowledge 0,142; relationship between semester and behaviour 0,256 and relationship between knowledge and behaviour 0,318. The conclusion of this study is the relationship between semester and knowledge are categoried very low with positive significant relationship. Relationship between semester and behaviour and relationship between knowledge and behaviour are categoried low with positive significant relationship. Keywords: behaviour, diarrhea, knowledge, self-medication Abstrak Swamedikasi dilakukan untuk mengatasi keluhan atau penyakit ringan seperti penyakit diare. Tingkat pengetahuan dan perilaku individu dalam penentuan dan penggunaan obat diare dapat mempengaruhi swamedikasi diare sehingga tidak terjadi penggunaan obat yang tidak rasional. Penelitian ini bertujuan mengetahui hubungan tingkat semester, pengetahuan dan perilaku mahasiswa farmasi Universitas Tanjungpura tahun 2021/2022 terhadap swamedikasi diare. Metode penelitian dilakukan secara retrospektif potong lintang berbentuk kuesioner. Metode stratified random sampling digunakan untuk pemilihan sampel. Analisis rank-spearman digunakan untuk menganalisis hubungan tingkat semester, pengetahuan dan perilaku responden terhadap swamedikasi diare. Berdasarkan penelitian menunjukkan bahwa dari 232 responden, mayoritas responden adalah perempuan, berusia 21 tahun, memperoleh obat dari apotek tanpa resep (81,03%), dan menggunakan obat diare golongan adsorben. Responden memiliki tingkat pengetahuan yang baik (9,91%), cukup (28,45%) dan kurang (61,64%) dan tingkat perilaku tepat (79,74%) dan tidak tepat (20,26%). Hasil p-value menunjukkan hubungan tingkat semester terhadap pengetahuan yaitu 0,142; hubungan tingkat semester terhadap perilaku 0,256 dan hubungan tingkat pengetahuan dan perilaku 0,318. Kesimpulan dari penelitian ini adalah terdapat hubungan signifikan positif berkategorikan sangat rendah pada tingkat semester terhadap pengetahuan dan hubungan signifikan positif berkategorikan rendah pada tingkat semester terhadap perilaku dan hubungan tingkat pengetahuan terhadap perilaku berkategorikan rendah. Kata Kunci: diare, pengetahuan, perilaku, swamedikasi